In vitro fertilization exacerbates stroke size and neurological disability in wildtype mice. (15th November 2021) - Bonetti, N.R.; Meister, T.A.; Soria, R.; Akhmedov, A.; Liberale, L.; Ministrini, S.; Dogar, A.; Lüscher, T.F.; Messerli, F.H.; Rexhaj, E.; Camici, G.G.; Beer, J.H.; et al.
Abstract: Background and purpose: Assisted reproductive technologies (ART) induce premature vascular aging in human offspring. The related alterations are well-established risk factors for stroke and predictors of adverse stroke outcome. However, given the young age of the human ART population there is no information on the incidence and outcome of cerebrovascular complications in humans. In mice, ART alters the cardiovascular phenotype similarly to humans, thereby offering the possibility to study this problem. Methods: We investigated the morphological and clinical outcome after ischemia/reperfusion brain injury induced by transient (45 min) middle cerebral artery occlusion in ART and control mice. Results: We found that stroke volumes were almost 3-fold larger in ART than in control mice ( P  < 0.001). In line with these morphological differences, neurological performance assessed by the Bederson and RotaRod tests 24 and 48 h after artery occlusion was significantly worse in ART compared with control mice. Plasma levels of TNF-alpha, were also significantly increased in ART vs. control mice after stroke ( P  < 0.05). As potential underlying mechanisms, we identified increased blood-brain barrier permeability evidenced by increased IgG extravasation associated with decreased tight junctional protein claudin-5 and occludin expression, increased oxidative stress and decreased NO-bioactivity in ART compared with control mice. Conclusions: In wildtype mice, ART predisposes to significantly worse morphological and functional stroke outcomes, related at least in part to altered blood-brain barrier permeability. These findings demonstrate that ART, by inducing premature vascular aging, not only is a likely risk factor for stroke-occurrence, but also a mediator of adverse stroke-outcome. Translational perspective: This study highlights that ART not only is a likely risk factor for stroke-occurrence, but also a mediator of adverse stroke-outcome. The findings should raise awareness in the ever-growing human ART population in whom these techniques cause similar alterations of the cardiovascular phenotype and encourage early preventive and diagnostic efforts. Highlights: This study highlights that ART is associated with larger stroke size, adverse functional stroke-outcome, likely due to increased blood brain barrier permeability, increased oxidative stress and decreased NO bioactivity. The findings should raise awareness in the ever-growing human ART population with similar alterations of the cardiovascular phenotype and encourage early preventive and diagnostic efforts.